(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The history of the establishment of the institution of the children’s ombudsman began in the second half of the 20th century, when the need arose to create a specialized body for the protection of children’s rights. This process was driven by international initiatives, especially after the adoption of the UN Convention on the Rights of the Child in 1989. The Convention set the basis for the establishment of national mechanisms such as the Children’s Ombudsman, who acts as an independent advocate for children’s interests.